Genius loci as a meta-concept - Vecco, Marilena (Journal of cultural heritage, 2020)
This research presents an analysis of the concept of genius loci over time. It aims to trace its evolution to provide its deeper understanding as a meta-concept. To this end, a holistic approach — including psychic, physical and human components — is taken to address its double nature of being both a reality and an entity. Genius loci is the intangible quality of a material place, perceived both physically and spiritually. It reveals itself through visible tangible and perceivable non-material features. It is also made known by underlying processes, because genius loci is a signifier of a process that is happening and cannot intentionally be created. It is significant in terms of being both the mediator and medium of social interactions. The analysis of genius loci's characteristics allows us to introduce first the concepts of hard and soft values accordingly to a human sustainable development perspective and secondly, the threefold process that should characterise it. This process is a fundamental requirement to preserve and transmit the genius loci.